Correlation analysis of circulating PCDH17 DNA methylation changes with rheumatoid arthritis patients - Fuyu Zhao; Mi Zhou; Jia Liu; Cen Chang; Ping Jiang; Kai Wei; Jianan Zhao; Yu Shan; Yixin Zheng; Yiming Shi; Yunshen Li; Yuejuan Zheng; et al. (Scientific Reports)
Abstract Analyze the correlation between the DNA methylation levels of Protocadherin 17 (PCDH17) cg03865667 and rheumatoid arthritis (RA), and evaluate its potential as a biomarker for diagnosing RA. Peripheral blood samples were collected from a cohort of 370 individuals, comprising patients diagnosed with RA, ankylosing spondylitis (AS), psoriatic arthritis (PsA), gout, systemic lupus erythematosus (SLE), dermatomyositis (DM), primary Sjögren’s syndrome (SS), and healthy controls (HC), for subsequent analysis.DNA methylation sequencing techniques were employed to evaluate the methylation levels of the PCDH17 cg03865667 locus. Relative to the HC, AS, and SS groups, PCDH17 cg03865667 was significantly downregulated in RA patients (P = 0.0403; p = 0.0290; p = 0.044). Compared to the HC group, the methylation levels at CpG sites 57,631,544, 57,631,571, and 57,631,581 were significantly downregulated in RA patients (p = 0.0078; p = 0.0123; p = 0.0309). For the TTCCTT and TTTCTT haplotypes, methylation levels were significantly lower in RA patients than in HC (p = 0.0188; p = 0.0053), particularly for the TTTCTT haplotype. Significant differences were observed between the CCP(-) RF(-) group, the CCP(+) / RF(+) group, and the HC group among the RA subgroups. No significant differences were found within the double-positive subgroup.The average methylation level of PCDH17 was negatively correlated with C-reactive protein (CRP) (r=-0.28, p = 6.9e-4). This study indicates that PCDH17 cg03865667 methylation may function as a potential biomarker for RA diagnosis. The subgroup analysis suggests that it may serve as a potential biomarker for diagnosing RA, indicating a capacity to enhance the diagnostic accuracy for seronegative RA and reduce the likelihood of missed and incorrect diagnoses.